In pursuit of societal harmony and officially multilingual countries Reviewing the experiences and approaches in officially monolingual - A'Beckett, Ludmilla; du Plessis, Theodorus (UJ Press, 2017)
In pursuit of societal harmony: Reviewing the experiences and approaches in officially monolingual and officially multilingual countries contains a selection of papers on language legislation that were presented at the International Conference on Language Policy in Multicultural and Multilingual Settings, Mandalay, Myanmar, 8-11 February 2016. The editors, both members of the International Academy of Language Law / Académie internationale de droit linguistique, brought together presentations that deal with language legislation and practices in Europe, Asia, Africa and North America. The contributions show that the post-communist trend in language policy has been vastly represented by attempts to eliminate the language, and even the cultural legacy, of the formerly hegemonic nation/s in countries emerging after the collapse of the system. In doing so officials in these countries tend to link the harmonisation of a diverse society with the idea of homogenising its population, and prioritising the cultural legacy of the titular nation. In contrast, some post-colonial countries are more tolerant of the language of their colonisers but consequently do not sufficiently promote the institutionalisation of their indigenous languages. Furthermore, the absence of visible efforts to follow any legal pattern in this regard often result in a communication gap between government and the various communities.